Project Portfolio Management: Methods and Options for Implementation - Aleksandrova, Matilda (Research Papers, 2008)
The paper reviews project portfolio management as an instrument for supporting organizational strategy implementation through a set of integrated projects. On the basis of a study of applied research work in this area a general model for project portfolio management is suggested. A range of methods for project portfolio management is also considered. Their application provides top management and project managers with in-depth and detailed approach revealing the way by which the execution of different projects can influence organizational success as a whole.